The effect of heat-treatment on SARS-CoV-2 viability and detection - Burton, Jane; Love, Hannah; Richards, Kevin; Burton, Christopher; Summers, Sian; Pitman, James; Easterbrook, Linda; Davies, Katherine; Spencer, Peter; Killip, Marian; Cane, Patricia; Bruce, Christine; et al. (Journal of virological methods, 2021)
•SARS-CoV-2 is not fully inactivated by heating to 56 °C or 60 °C for up to 60 min.•Complete inactivation occurred at 80 °C for 90 min or 95 °C for 1 or 5 min.•Heating SARS-CoV-2 to 80 °C for more than 30 min results in increased Ct values.•Significant variation in inactivation efficacy occurred between replicate samples.•Due to variability heat-inactivation protocols require local validation. The development of safe diagnostic protocols for working with SARS-CoV-2 clinical samples at Biosafety Level 2 (BSL2) requires understanding of the effect of heat-treatment on SARS-CoV-2 viability and downstream RT-PCR sensitivity. In this study heating SARS-CoV-2/England/2/2020 to 56 °C and 60 °C for 15, 30 and 60 min reduced the virus titre by between 2.1 and 4.9 log10 pfu/mL (as determined by plaque assay). Complete inactivation did not occur and there was significant variability between replicates. Viable virus was detected by plaque assay after heat-treatment at 80 °C for 15 or 30 min but not 60 or 90 min. After heat-treatment at 80 °C for 60 min infectious virus was only detected by more sensitive virus culture. No viable virus was detected after heating to 80 °C for 90 min or 95 °C for 1 or 5 min. RT-PCR sensitivity was not compromised by heating to 56 °C and 60 °C. However, RT-PCR sensitivity was reduced (≥3 Ct value increase) after heating the virus to 80 °C for 30 min or longer, or 95 °C for 1 or 5 min. In summary we found that the efficacy of heat-inactivation varies greatly depending on temperature and duration. Local validation of heat-inactivation and its effects downstream is therefore essential for molecular testing.